The influence of aerobic performance on HRR in road cyclists and footballers - Kamil Michalik; Artur Woźniak; Iwona Wierzbicka-Damska (Kazimierz Wielki University, 2017)
Introduction. Effective heart rate recovery is associated with higher levels of aerobic performance Aim. The aim of this study was to investigate the relationship between level of aerobic performance describe of maximal oxygen uptake (VO2max) value and heart rate recovery (HRR) in road cyclist and footballers.   Materials and methods. The study involved of 30 male trainees football in the Polish second leauge (n = 9) and road cyclists, members of the professional clubs (n = 21). Road cyclist were divided into terms of level VO2max into two groups RC1 (higher value) and RC2(lower value), based on the incremental exercise test. The test was performed on cycloergometer, and after the completion of the test for 5 minutes stayed seated for recorded of HRR. Results. The differences were not statistically significant. In the course of fast phase restitution lowest values showed subjects from the group of football players We also used a relative values with respect to the maximum heart rate (HRmax), and no significant differences were found between the groups. In any group there was no statistically significant correlation between the variables related to the HRR and the level of VO2max. Conclusions. Restitution of the fastest heart rate, also in relation to the HRmax was observed in the group of footballers. Road cyclists despite significant differences in the level of aerobic performance do not differ significantly of HRR.